Impact of Foreign Remittances on Ghanaian Economic Growth: An Assessment of the Mediating Role of Mobile Phone Technology - Zubairu, Ibrahim; Alenezi, Marim; Iddrisu, Ahmed Jamal; Amankwanor, Essel Francis (Business, Management and Economics: Research Progress Vol. 7, 2024)
The aim of the study was to investigate how remittance inflows affect economic growth while taking the mobile phone technology's mediating function into account. Ghana was the subject of the 46-year study, which ran from 1975 until 2020. The Ordinary Least Square regression model was employed in the investigation. The findings showed that remittance inflow had a small but negative impact on economic growth in the absence of the interaction effect. The analysis finds a strong positive correlation between the introduction of an interactive term (mobile phone technology) and economic growth. Mobile Phone Technology showed a strong positive correlation with economic growth, but remittances showed a negligible positive correlation. According to the study, life expectancy, exchange rates, and foreign direct investment (FDI) are the main factors influencing economic growth. The study's findings indicate that in order to maximize the benefits of foreign remittances on economic growth, policymakers should establish a suitable technological framework for their management and utilization. This will improve financial inclusion, lower transaction costs, and encourage the effective use of funds.